Lived Experiences of Couples Regarding Grief Caused by Recurrent Miscarriages in Infertile Women: A Phenomenological Study - Zaraj , Hoda; Firoozi, Manijeh; Vakilian , Katayon; Nosrati , Fatimah (Psychology of Woman Journal, 2026)
Objective: This study aimed to gain an in-depth understanding of couples’ lived experiences of grief caused by recurrent miscarriages in infertile women.Methods and Materials: This qualitative study was conducted using a descriptive phenomenological approach. Seventeen participants (14 women and 3 men) with a history of at least two consecutive miscarriages and infertility were purposively selected from specialized infertility centers in Tehran and Qom in 2025. Data were collected through semi-structured interviews (individual and couple interviews) and analyzed using Colaizzi’s seven-step method.Findings: Six main themes emerged: emotional turmoil (shock, anxiety, guilt, chronic sorrow, and hopelessness); continuity of loss (multilayered, disenfranchised, and complicated grief); distorted self-concept (sense of bodily defectiveness, doubts about gender identity, and reduced self-esteem); the relationship under the shadow of loss (mutual empathy, distance resulting from differences in grieving styles, and strengthened bond); coping and adaptation (individual strategies, social support, and the role of healthcare staff); and search for meaning (religious meaning-making, post-traumatic growth, and redefinition of goals).Conclusion: Recurrent miscarriage is an existential, relational, and culture-based phenomenon. Grief in this context is multilayered, chronic, and often overlooked. A deep understanding of this experience can contribute to the design of couple-centered interventions and enhance healthcare providers’ sensitivity.